The effect of methyl jasmonate on morpho-physiological and biochemical parameters and mineral contents in Satureja khuzistanica Jamzad under salinity stress - Amir Saadatfar; Samira Hossein Jafari (Journal of Medicinal Plants, 2022)
Background: Satureja khuzestanica is an endemic medicinal plant that widely distributed in the northern Khuzestan and southern Lorestan provinces of Iran. Objective: In this study, simultaneous effects of methyl jasmonate (MeJA) and salinity on morpho-physiological parameters and minerals contents in S. khuzistanica were studied. Methods: Different salt levels (0, 3, 6 and 9 dS/m) were applied during growth period for one month. MeJA spraying at 0, 60 and 120 µM concentrations performed three times for one week. Samples were taken during flowering stage. Results: The results showed that MeJA × salt interaction had significant effects on all morpho-physiological and biochemical parameters of S. khuzestanica (P < 0.01). The highest stem length, root length, fresh and dry weights were observed at 60 and 120 µM MeJA without salt. The amounts of chlorophyll, N, P, K+, K+/Na+, Ca2+ and Mg2+ had significant reductions with increasing salt levels. The highest amounts of these parameters were observed at 60 µM MeJA without salt. There were significant enhancements in total phenol, antioxidant activity, proline, sugar and Na amounts with increasing salt levels. The highest content of total phenol and antioxidant activity was induced at 60 µM MeJA × 6 dS/m salt (2.22 and 50.23 %, respectively). The 9 dS/m salt treatment at 60 µM MeJA had the highest sugar (1.69 mg/g) and proline (0.29 mg/g) contents. Conclusion: Totally, 60µM MeJA concentration caused the best performance of savory under salt stress. Therefore, MeJA application can be helpful to alleviate negative effects of salt in S. khuzistanica.